TheoMedia the Media of God and the Digital Age. - Byers, Andrew (Havertown : The Lutterworth Press, 2014)
This book is a hermeneutical project in the church's wider efforts of trying to understand the technological mediascape of the twenty-first century. The purpose is not to offer a how-to guidebook to help churches incorporate communications technology into their worship and witness. Byers provides something more foundational, the beginnings of a way of constructing a theological frame of reference for understanding and appropriating media in the digital age and in the ages to come.
Chapter 12. Resurrection & Ascension Word-media, Baptism, and Christ as MediatorTheoMedia Note 9 Word versus Image? Dismembering the Sensorium ... and Christ's Body?; Chapter 13. Christ's Return: Apocalyptic Media and the End of Mediation; Part 5: Conclusion; Chapter 14. The Spirit and the Bride: A Rough Theological Framework and "EcclesioMedia"; Bibliography; Back cover.
Print version record.
Master record variable field(s) change: 072
Keywords: Technology -- Religious aspects -- Christianity; Digital communications -- Religious aspects -- Christianity; Mass media -- Religious aspects -- Christianity; Internet -- Religious aspects -- Christianity; Technology -- Influence; Digital communications -- Influence; Mass media -- Influence; Internet -- Influence; Christianity and culture; RELIGION -- Christian Ministry -- Missions; RELIGION / Christian Theology / General; Electronic books